Efficacy of ionic silver solution on shelf life extension of khoa - MH, SATHISH KUMAR (Indian Journal of Dairy Science, 2018)
Silver has been reported as a powerful antimicrobial agent that has been used for thousands of years, with no reported harmful side effects. Ionic silver solution (ISS) with 11 and 17 ppm concentration was prepared by electrochemical method and were separately added into milk @ 2 % (v/w on milk basis) and khoa was prepared from that milk. In another treatment, ISS with 11 ppm and 17 ppm were separately added @ 2 % (v/w on milk basis) during pat formation stage. Results shows that when ISS of 11 ppm and 17 ppm were added into milk no significant reduction of microbes was noticed, however, when ISS of 11 ppm and 17 ppm added at the pat formation stage there was 7% and 18.18% reduction in TBC and 3.33% and 10% reduction in Y&M counts were observed as compared to control khoa sample, respectively. Khoa added with 17 ppm ISS at pat formation showed highest reduction in microbial count, hence selected for storage study. Khoa was packaged in polystyrene tubs and stored at 7Â±1Â°C for shelf life study. Shelf life of the control khoa sample was found to be 14 days, whereas treated khoa sample was stable up to 17 days. No significant difference (p>0.05) was observed in sensorial quality parameters and physico-chemical parameters during storage.